The role of vitamin D on rotator cuff tear with osteoporosis - Guan, Zhiyuan; liu, shengfu; luo, liying; Guan, Zhiqiang; zhang, qinggang; tao, kun (Frontiers in Endocrinology, 2022)
Backgrounds Osteoporosis (OP) is an important risk factor for rotator cuff injury(RCTs). However, the relationship and mechanism between rotator cuff injury and osteoporosis are unclear. Therefore, to investigate association between rotator cuff injury and osteoporosis, and find clinical characteristics, bone mineral density, bone metabolism markers, and nutrient levels in rotator cuff injury patients with or without osteoporosis. Methods One hundred and four cases of patients (RCTs, n=32; RCTs-OP, n=72) who underwent rotator cuff injury and need arthroscopic rotator cuff repair between June 2021 and February 2022, along with the diagnosis of osteoporosis were identified from the DXA. The outcome measure includes clinical characteristics, bone mineral density, bone metabolism markers, vitamins, and amino acids. Multivariable logistic regression analysis was applied to build a predicting model incorporating the feature selected in the least absolute shrinkage and selection operator regression model. Discrimination, calibration, and clinical usefulness of the predicting model were assessed using the C-index, calibration plot, and decision curve analysis. Internal validation was assessed using bootstrapping validation. Results OP with RCTs has a lower level of in 25-vitD, OCN, serum Ca2+, ornithine, diaminocaproic_acid but the high level of Vitamin_B12, PTH, Vitamin_D3,γ_aminobutyric_acid, Vitamin_C and Vitamin_E than RCTs patients without OP. Predictors contained in the prediction nomogram included lumber T score, femur T score, Niacin_B3, and vitamin D, reflecting the combined effect of vitamins on RCTs-related OP progression. The model has good discriminative ability with a C-index of 0.938(95% CI:-1.83-1.39) and good scaling ability. The high C-index value of 0.95 is still achievable with range validation. Analysis of decision curves showed that non-adherence is clinically useful when intervention decisions are at the 14% probability limit of non-adherence. Conclusion This study supports the hypothesis that lumber T score, femur T score, Niacin_B3, and Vitamin D are valuable prognostic biomarkers on RCTs related OP progression.